The Crystal Structure of Bubbles in the Wet Foam Limit (Amendment) - WEAIRE, DENIS LAWRENCE; HUTZLER, STEFAN (Royal Society of Chemistry, 2006)
We have observed a rich variety of three-dimensional crystal and defect structures spontaneously formed by small (diameter 200 mm) bubbles in a wet foam. The observations confirm and extend those made by Bragg and Nye in 1947. However, while their experiments with two-dimensional bubble rafts have stimulated many researchers, their work on three-dimensional wet assemblages does not appear to have been followed up. These ordered packings now pose intriguing questions for the physics of foams. The bubbles seem too large for conventional thermodynamics and kinetics to easily explain the high degree of ordering.
PUBLISHED
Keywords: Physics